Revitalizing the Quality of Waste Management Services Based on Public Awareness - Nur Kasmiati; Hayat; Septina Dwi Rahmawati (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Waste services in Bima City, West Nusa Tenggara. It is an important aspect in maintaining environmental cleanliness and health. This research aims to examine the refitalization of waste management quality based on community awareness. To realize that, it is necessary to transform services using 5 (five) dimensions of public service quality, namely (tangible), reliability, responsiveness, assurance, and empathy. This research uses a descriptive qualitative approach with data collection techniques through observation, documentation studies, and in-depth interviews with informants. The conclusions drawn are as follows, waste management in Bima City mostly already has indicators of service quality dimensions. But there are still some indicators that have not been fulfilled, so that they become obstacles in the Waste Management Service process. Among other things, inadequate facilities and infrastructure, human resources officers in handling waste, and lack of public awareness in terms of waste. Thus, it is necessary to add supporting infrastructure, additional human resources officers and educational programs for the community related to waste problems in order to achieve quality services in Bima City by the Environmental Service.